Proceedings of the 4th International Conference on 3D Body Scanning Technologies, Long Beach CA, USA, 19-20 November 2013 2013
DOI: 10.15221/13.041
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of 3D Scanning in Establishing Sideseam Placement for Pattern Design

Abstract: As woven garments are cut from flat pieces of cloth, pattern cutting methods must create flat 2D shapes that are constructed to form 3D garments that fit a particular body shape. The placement of sideseams represents a key division of the pattern where the front and back portions of a garment relating to a particular body measurement are distributed to create a balanced garment. During most pattern creation methods the distribution of the measurement into back and front arcs is proportionally determined by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…This relates better to how the measurement is applied in the pattern [1]. This also brings for consideration the difficulties of side seam placement highlighted by earlier research [24], [25]. A further important consideration is the ISO 8559 [17] determines the bust point as the most anterior projection.…”
Section: Comparable Measurements Produced By the Body Scannersmentioning
confidence: 99%
See 1 more Smart Citation
“…This relates better to how the measurement is applied in the pattern [1]. This also brings for consideration the difficulties of side seam placement highlighted by earlier research [24], [25]. A further important consideration is the ISO 8559 [17] determines the bust point as the most anterior projection.…”
Section: Comparable Measurements Produced By the Body Scannersmentioning
confidence: 99%
“…Here, the measurements defined manually and those defined by the body scanner can be seen to be comparable. Should this arc division not be captured through measurement, it will be imposed within the draft process [24]. However, careful consideration of the suitability waist location in 3D Body Scanning is required to make sure that measurements are comparable and suitable [26].…”
Section: Waist and Hip Girthsmentioning
confidence: 99%
“…Neither do the texts inform as to how the percentage of division should affect pattern-drafting for body shape. [16], [17] It has been suggested that automated virtual garment design can only be useful to fashion designers when the 3D and 2D CAD environments are driven by artificial neural networks mimicking the nonlinear thinking of humans. [18] For this to be realized, the iterative nature of pattern-drafting and the myriad of heuristic practices umbrellaed under the subjective garment fit label must be thoroughly and mathematically understood.…”
Section: Discussionmentioning
confidence: 99%
“…Other research has explored side seam placement and customized darting as ways to assess body shape, where body shape is predominantly affected by front-to-back variations. [17] However, the results of such research are infrequently applied in practice. Intelligent Shaping® software, using the Clone Block® method of pattern-engineering, leads us to support a direct body-to-2D pattern relationship.…”
Section: Introductionmentioning
confidence: 99%
“…Variations in methods of body segmentation for anthropometric assessment [52,61,62,63,64,65] do not necessarily correlate to logical pattern engineering landmarks. Methods for taking arc (half body) measurements [53,21] produce further inconsistencies due to how side seams are assigned [11,21,66,41]. Traditional pattern drafting methodologies cannot produce a suitable fit on all body shapes [67,68,20,34,22].…”
Section: Landmarksmentioning
confidence: 99%